Recovery of injured Broca's portion of arcuate fasciculus in the dominant hemisphere in a patient with traumatic brain injury. Issue 51 (December 2017) - Jang, Sung Ho; Ha, Ji Wan; Kim, Hyun Young; Seo, You Sung
Abstract: Rationale: Recovery of injured AF in patients with traumatic brain injury (TBI) has not been reported. In this study, we report on a patient with TBI who recovered from an injury to Broca's portion of AF in the dominant hemisphere, diagnosed by diffusion tensor tractography (DTT). Patient concerns: A 28-year-old right-handed male patient suffered head trauma resulting from sliding while riding a motorcycle. Diagnoses: He was diagnosed with a traumatic contusional hemorrhage in the left frontal lobe, subarachnoid hemorrhage, and subdural hemorrhage in the left fronto-temporal lobe. Interventions: He underwent craniectomy on the left fronto-temporal area, and hematoma removal for the subdural hemorrhage in the neurosurgery department of a university hospital. Two weeks after the injury, he was transferred to the rehabilitation department of another university hospital. He showed severe aphasia and brain MRI showed leukomalactic lesion in the left frontal lobe. Outcomes: The result WAB for the patient showed severe aphasia, with an aphasia quotient of 45.3 percentile. However, his aphasia improved rapidly by 9 months with an aphasia quotient at the 100.0 percentile. 2-week DTT detected discontinuity in the subcortical white matter at the branch to Broca's area of left AF. By contrast, on 9-month DTT, the discontinued portion of left AF was elongated to the left Broca's area. Lessons: Recovery of injured Broca's portion of AF in the dominant hemisphere along with excellent improvement of aphasia was demonstrated in a patient with TBI. This study has important implications in brain rehabilitation because the mechanism of recovery from aphasia following TBI has not been elucidated.